EdTech for Marginalised Learners in Southeast Asia: Perspectives from funders and providers on priorities, design, investment, and scaling considerations - Jayasinghe, Neema; Chrisani, Aprillia; Honda, Delanie; Gunawan, Clarissa Jazzlyne (EdTech Hub, 2025)
This report presents the findings of a landscape analysis of EdTech interventions designed for the Southeast Asian context. The analysis aims to understand the extent to which EdTech providers and funders in Southeast Asia address the needs of marginalised learners through their priorities in design, investment, and scaling decisions. It focuses on initiatives targeting marginalised groups and those with potential to scale. The research for the study included interviews with funders engaged in the Southeast Asian EdTech space to examine their perspective on EdTech’s impact on marginalised learners, the approaches they adopt to support inclusive solutions, and the drivers behind their investment decisions. This builds on EdTech Hub’s research for the ASEAN-UK SAGE programme, particularly on how EdTech could be used to support improvements in foundational literacy and numeracy, out-of-school children and youth, and learners with disabilities, as well as overcoming gender barriers to employment through the use of EdTech solutions. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Technology-Enabled Psychosocial Support Interventions for Education in Emergencies - Moustafa, Nariman; Mtungwa, Nothando (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Teaching and Learning of Mathematics in the Context of the National Numeracy Programme in Malawi: Findings from a rapid in-depth qualitative study - Correa de Oliveira, André; Kanyoza, Charity; Smart, Theresa; Lurvink, Anne-Fleur; Boilo, Violet; Kadzamira, Esme; Haßler, Björn (EdTech Hub, 2024)
To inform the development of Malawi's National Numeracy Programme (NNP), EdTech Hub worked with the Directorate of Quality Assurance Services (Malawi), Cambridge Education, and the UK Foreign, Commonwealth and Development Office (FCDO) to examine the NNP’s components during its extended pilot phase during the 2022–2023 school year, and explore how these might be refined to improve teaching and learning of mathematics in Malawi. In-depth qualitative research in four schools was undertaken to obtain feedback on the programme’s components from teachers, head teachers, and Primary Education Advisors. The study’s methodology incorporated semi-structured interviews, focus group discussions, lesson observations, learning circle observations, training observations, and ethnographic methods. Additionally, a mathematics specialist conducted an independent, in-depth, desk-based review of the NNP teaching and learning resources to refine the study’s analysis. This report summarises the principal findings from the study. Keywords: Malawi, mathematics, numeracy, teacher continuous professional development, teacher learning circles An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen